Peran Karakteristik Sistem dalam Meningkatkan Kinerja Organisasi : Library Research - Ariana Ariana; Saila Rahma Annisa Nst; Bintang Ridzky Dwi Putra; Abdul Fattah Nasution (Student Research Journal, 2024)
This research addresses the role of system characteristics in improving organisational performance, focusing on how management information systems can contribute to operational efficiency and better decision-making. The background to this research is based on the importance of coordination and integration between departments in complex organisations, as well as the need to respond quickly to market changes. The purpose of this research is to explore the characteristics of systems that can improve organisational performance and identify gaps in previous research. The method used was desk research, which involved analysing relevant literature and scholarly journals. The findings show that system characteristics not only improve information flow and operational efficiency, but also support real-time decision-making, although there are some gaps that need to be further explored in future research